2022
DOI: 10.1155/2022/2549413
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcome of Sepsis in Traumatic Patients and Pathogen Detection Using Metagenomic Next-Generation Sequencing

Abstract: Objective. Sepsis, a life-threatening clinical syndrome, is a leading cause of mortality after experiencing multiple traumas. Once diagnosed with sepsis, patients should be given an appropriate empiric antimicrobial treatment followed by the specific antibiotic therapy based on blood culture due to its rapid progression to tissue damage and organ failure. In this study, we aimed to analyze the risk factors and outcome of sepsis in traumatic patients and to investigate the performance of metagenomic next-genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 45 publications
(49 reference statements)
1
8
0
Order By: Relevance
“…Temperature : Among patients with sepsis aged ≥65 years, the mean temperature was greater than that of patients without sepsis. Significantly greater temperatures in trauma patients with sepsis were also observed in a study by Tong et al; however, the patients were not separated into different age groups [ 25 ].…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…Temperature : Among patients with sepsis aged ≥65 years, the mean temperature was greater than that of patients without sepsis. Significantly greater temperatures in trauma patients with sepsis were also observed in a study by Tong et al; however, the patients were not separated into different age groups [ 25 ].…”
Section: Discussionmentioning
confidence: 59%
“…However, in a study by van Wessem et al, severely injured patients ≥70 years did not develop more infectious complications (such as sepsis) than younger patients did [ 24 ]. Similarly, Tong et al and Chung et al demonstrated that age is not a significant risk factor for sepsis in patients with multiple traumas [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations